Macrovascular and microvascular complications in type 2 diabetic Iraqi patients treated by metformin and glibenclamide versus metformin and sitagliptin - abbas, Hassan; Al-Shamaa, Kassim; Al-Rubai, Salim (Iraqi National Journal of Nursing Specialties, 2012)
Background: In type 2 diabetes mellitus there is a progressive loss of beta cell function. One newapproach yielding promising results is the use of the orally active dipeptidyl peptidase-4 (DPP-4)inhibitors for type 2 diabetes mellitus.Objective: This study aims at comparing the possible occurrence of macrovascular & microvascularcomplications in Iraqis patients with type 2 diabetes mellitus using two combinations of drugsmetformin + glibenclamide and metformin + sitagliptin.Methodology: Sixty eight T2DM patients and 34 normal healthy individuals as control group wereenrolled in this study and categorized in to two treatment groups. The group 1 (34 patients ) receivedmetformin 500 mg three times daily + glibenclamide 5 mg twice daily and the group 2 (34 patients)received metformin 500 mg three times daily + sitagliptin 100 mg once daily. The urine sample wascollected for estimation of microalbumin urea and patients' examination was made by specialistconsultant endocrinologist.56Results: The percentages of microalbuminurea were significantly (p